Effects of cotton cultivars differing in gossypol content on the quality of Aphis gossypii as prey for two species of Coccinellidae - Correa, L. R. B. [UNESP]; Cividanes, F. J. [UNESP]; Gontijo, L. M.; Santos-Cividanes, T. M. [UNESP] (Taylor & Francis Ltd, 2014)
Plants can have detrimental effects on biological control agents by affecting their prey or host quality. Thus, it is important to understand the tri-trophic interactions between plants, herbivores and natural enemies when implementing biological control programmes. Studies have shown that both morphological and chemical traits of host plants can affect the third trophic level. Cotton plants are known to produce alkaloids such as gossypol, a sesquiterpene aldehyde that can confer resistance against herbivorous arthropods. Nevertheless, little is known about the effect of gossypol on biological control agents. In this study, we investigated how three cotton cultivars (BRS Rubi, BRS Safira and BRS Verde) differing in gossypol content affect development and growth of predatory coccinellids, Eriopis connexa and Harmonia axyridis, feeding on the cotton aphid Aphis gossypii reared on those cultivars. The results show that the cultivar BRS Rubi (highest gossypol content) had a sub-lethal effect on the development and growth of both Coccinellidae species compared with the other cultivars. Overall, the cultivar BRS Rubi reduced slightly fecundity, net reproductive rate and intrinsic rate of natural increase for both Coccinellidae species. However, because aphid populations stay short periods of time in the field, and adult coccinellids may supplement its diet with alternative prey and plant material this sub-lethal indirect effect of gossypol may not have a detrimental effect on field biological control of cotton aphid by either E. connexa or H. axyridis, thus suggesting a compatibility between plant resistance and biological control agents.
Keywords: coloured cotton; gossypol; Aphis gossypii; Coccinellidae; tri-trophic interactions; biological control